Should We Consider Heart Rate Reduction in Cardiac Transplant Recipients?. Issue 2 (21st August 2012) - Sekar, Baskar; Critchley, William R.; Williams, Simon G.; Shaw, Steven M.
Abstract Increased resting heart rate is an independent modifiable risk factor for the development of cardiovascular disease. Numerous studies have demonstrated improved clinical outcomes with heart rate reduction in patients with coronary artery disease and heart failure, but its role in transplanted hearts is not yet established. Sinus tachycardia is more common in heart transplant recipients due to graft denervation. Although a large number of studies have recognized increased heart rate as a predictor of native coronary artery atherosclerosis and overall cardiac mortality, contradicting results have been observed in heart transplant recipients. There is no clear consensus about what the normal range of heart rate should be following heart transplantation. The aim of this article was to review the literature to evaluate whether heart rate reduction should be considered in heart transplant recipients. Dr. Simon G. Williams and Dr. Steven M. Shaw have received honoraria from Servier for advisory work. The authors have no other funding, financial relationships, or conflicts of interest to disclose.